2004
DOI: 10.1080/13607860410001709737
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of leisure time satisfaction in family caregivers

Abstract: Caregiving is known to limit participation in a variety of roles. Leisure roles are increasingly recognized as important for the well-being of older adults. Little is known, however, about the impact of caregiving on leisure activities, and existing measures are of limited utility in caregiving research. We developed the Leisure Time Satisfaction (LTS) measure to allow further study of the impact of caregiving on caregivers' leisure time satisfaction, the role of leisure in understanding the caregiving process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 27 publications
1
62
0
1
Order By: Relevance
“…Although the differences between raw values of time dedicated to obligatory activities were significant, the studies analyzed showed that time spent on care is longer for informal caregivers than for formal caregivers (24,33) , for spouses than for those who are not spouses of elderly receiving care (28,30,(32)(33) , for those living with individuals who receive care (12) , for lowincome caregivers (12) , for those who have health problems (26,33) , for those who rely on more than one caregiver (26) and for those who have less information about how to care, have little access to specialized medical care and reduced experience concerning the management of psychiatric and behavioral disorders associated with dementia (28,(30)(31) . There was an inverse relationship between time dedicated to care and the level of behavioral competence of those receiving care (12,19,(21)(22)34) . The time dedicated to obligatory activities is spent on support for IADLs and BADLs and on supervision when dealing with behavioral problems associated with dementia (20,22,28,30,32,34) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the differences between raw values of time dedicated to obligatory activities were significant, the studies analyzed showed that time spent on care is longer for informal caregivers than for formal caregivers (24,33) , for spouses than for those who are not spouses of elderly receiving care (28,30,(32)(33) , for those living with individuals who receive care (12) , for lowincome caregivers (12) , for those who have health problems (26,33) , for those who rely on more than one caregiver (26) and for those who have less information about how to care, have little access to specialized medical care and reduced experience concerning the management of psychiatric and behavioral disorders associated with dementia (28,(30)(31) . There was an inverse relationship between time dedicated to care and the level of behavioral competence of those receiving care (12,19,(21)(22)34) . The time dedicated to obligatory activities is spent on support for IADLs and BADLs and on supervision when dealing with behavioral problems associated with dementia (20,22,28,30,32,34) .…”
Section: Resultsmentioning
confidence: 99%
“…There was an inverse relationship between time dedicated to care and the level of behavioral competence of those receiving care (12,19,(21)(22)34) . The time dedicated to obligatory activities is spent on support for IADLs and BADLs and on supervision when dealing with behavioral problems associated with dementia (20,22,28,30,32,34) . The increase in the number of hours dedicated to care, especially time for supervision, is also associated with the development of dementia (21)(22)(25)(26)(32)(33)(34) and advance in age of those receiving care (32) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations